2015
DOI: 10.2507/ijva.1.1.7.7
|View full text |Cite
|
Sign up to set email alerts
|

Creative Tourism In Destination Brand Identity

Abstract: This paper analyses the emerging trends in creative tourism, as well as the possibilities of developing creative offer as a means of sustainable development (protection of resources, socio-cultural elements, natural elements and improving the local population's standard of living) of small historic towns on the Opatija Riviera (Volosko, Kastav, Lovran, Veprinac, Mošćenice, Brseč). It further analyses the current state of creative offer, sets the goals and suggests some possible strategies for developing creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…This difference was also shown to be significant. This result confirms Shore (as cited in Stipanovic & Rudan, 2014), who suggested that the demand for local cultural experiences is gaining prominence among international travelers who want a more authentic experience when they travel overseas. International visitors not only want to see the main cultural heritage sites, but they also want to immerse themselves in the culture.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This difference was also shown to be significant. This result confirms Shore (as cited in Stipanovic & Rudan, 2014), who suggested that the demand for local cultural experiences is gaining prominence among international travelers who want a more authentic experience when they travel overseas. International visitors not only want to see the main cultural heritage sites, but they also want to immerse themselves in the culture.…”
Section: Resultssupporting
confidence: 85%
“…Developing creative tourism as part of the tourism product of a destination is however dependent on various aspects, for example: the stakeholders of the destination’s own creativity are vital for creative tourism; the cultural and natural values and assets of the destination should not be destroyed by the development of tourism, in other words, the development should be built on the principles of sustainability; and last, even destinations that do not possess ample cultural assets can develop creative tourism, which could improve the destination’s current tourism product (Stipanovic & Rudan, 2014).…”
Section: Discussion: Exploring Creative Tourism Potential In the Knpmentioning
confidence: 99%
See 1 more Smart Citation
“…In conjunction with the now-congested global market, it has been suggested that to truly involve tourists and remain competitive, products and services should be replaced with experiences and activities. Hence, cities and regions are choosing creative and sustainable strategies that complement the distinctive and notable images of their destinations [18,19].…”
Section: Creative Tourism and Destination Managementmentioning
confidence: 99%
“…Moreover, the tourism destination office is compelled to offer appealing experiences such as local traditions to visitors, which encourages active interactions between them and the tourism destination as well as the residents [6]. Regardless, market analyses to understand the type of co-creating activities that tourists are seeking should be taken into consideration due to the disparity between tourists' desires and consumption [19]. As specified by Bosnić et al [26], DMO ought to plan, organize, and control, but also inspire their workers to invest in education and training.…”
Section: Managerial Competenciesmentioning
confidence: 99%